Development of a computer-aided design and finite-element analysis combined method for customized Nuss bar in pectus excavatum surgery - Longhan Xie (Nature Portfolio, 2017)
Abstract Pectus excavatum (PEX) is the most common chest deformity in children, which is usually corrected by using the minimally invasive Nuss method. The orthopedic effect of the Nuss operation is mainly evaluated by both the Haller index and the appearance of the chest wall configuration, which is dependent on the operator’s clinical experience to a great extent. To improve the orthopedic effect, we proposed a novel method to individually design and optimize the shape of the Nuss bar and to advise its location as well as the incisions. By using the CT imaging data, the three-dimensional model of the PEX thoracic structure is reconstructed, which is further employed in finite element analysis to determine the operation plan. By referring to a healthy person who has similar chest dimensions to the PEX patient, the Nuss bar shape is designed, and according to the finding that the healthy chest wall boundary is almost convex with positive curvature, the Nuss bar shape is tuned to be a convex curve to ensure the orthopedic effect. Finite element analysis is employed to analyze the orthopedic effect and to determine the incision position of the Nuss bar. Experiments were carried out to verify the orthopedic effect of the customized Nuss bar, which showed that this method is more accurate and individualized, compared to conventional methods.